THICKNESS EFFECTS ON THE PHYSICAL CHARACTERIZATION OF NANOSTRUCTURED CUO THIN FILMS (International Journal of Food and Nutritional Sciences, 2023)
Nanostructured CuO thin films on glass substrates of varying thicknesses (250, 300, and 350 nm) were produced in these investigations using radio frequency (RF) magnetron sputtering. The films' X-ray diffraction (XRD) results showed a polycrystalline structure, with the (111) plane being the most prominent peak. Grain size was calculated using the Scherrer formula. As the film thickness increases from 250 nm to 3000 nm and then 300 nm, the average grain sizes decrease and reach 10.78 nm, 11.36 nm, and 11.84 nm, respectively. Nucleus scan microscopy (AFM) results showed that surface roughness dropped from 9.30 nm to 4.71 nm with increasing thickness. The root mean square (RMS) roughness also dropped from 9.18 nm to 4.29 nm as the layer thickness increased. Scanning electron microscopy (SEM) pictures show that the particles in the homogeneous, semi-spherical structure are evenly dispersed.